Wind turbine participation in micro‐grid frequency control through self‐tuning, adaptive fuzzy droop in de‐loaded area. Issue 2 (13th May 2019) - Abazari, Ahmadreza; Ghazavi Dozein, Mehdi; Monsef, Hassan; Wu, Bin
Abstract : The purpose of this research is to present an innovative load frequency control in the presence of wind turbines in islanded micro‐grid (MG). As islanded MG suffers from low inertia and insufficient primary frequency response (PFR), utilising the variable wind turbines in de‐loaded area can be considered as an alternative solution to deal with frequency control problems. In this context, the de‐load area is referred to a region where wind turbines release their stored kinetic energy in rotational masses following frequency disturbances. For effective utilisation of wind turbines, a self‐tuning, adaptive fuzzy droop is proposed, whose membership function parameters are optimised through artificial bee colony algorithm based on a multi‐objective decision making process. A comparison is made between the obtained results of the self‐tuning, adaptive fuzzy droop with conventional proportional integral derivative droop control in order to assess the proposed method performance in different disturbances.